Nonthermal Effects of Radar Exposure on Human: A Review Article - vida zaroushani; Ali Khavanin; seyed Bagher Mortazavi (Iranian Journal of Health, Safety and Environment, 2014)
ABSTRACT Microwave is part of the electromagnetic spectrum that has different application such as communications, military, air-traffic Control and etc... Previous studies showed that radar frequency could be a health hazard agent. This review article mentioned some of the studies that investigated non-thermal effects of radar frequencies. Reproductive effects, cancers, blood effects, genetic, adverse immune effects and mental effects are non-thermal effects that presented in this report. There are many unknown aspects of the biological effects and many of them did not determined very well such as oxidative stress and mental effects. Compliance with permissible exposure limits, reduction in exposure, and shielding are some of the controlling methods to protect workers from the exposure of microwave and among them, The use of shielding is a superior method for prevention of microwave exposure and among them, electromagnetic Nano composites shields is appropriate for protection of workers from radar exposure.